Fluorescence-guided tumor detection with a novel anti-EpCAM targeted antibody fragment: Preclinical validation. (March 2019) - Boogerd, Leonora S.F.; Boonstra, Martin C.; Prevoo, Hendrica A.J.M.; Handgraaf, Henricus J.M.; Kuppen, Peter J.K.; van de Velde, Cornelis J.H.; Fish, Alexander; Cordfunke, Robert A.; Valentijn, A. Rob P.M.; Terwisscha van Scheltinga, A.G.; MacDonald, Glen C.; Cizeau, Jeannick; et al.
Abstract: Tumor-specific fluorescent imaging agents are moving towards the clinic, supporting surgeons with real-time intraoperative feedback about tumor locations. The epithelial cell adhesion molecule (EpCAM) is considered as one of the most promising tumor-specific proteins due its high overexpression on epithelial-derived cancers. This study describes the development and evaluation of EpCAM-F800, a novel fluorescent anti-EpCAM antibody fragment, for intraoperative tumor imaging. Fab production, conjugation to the fluorophore IRDye 800CW, and binding capacities were determined and validated using HPLC, spectrophotometry and cell-based assays. In vivo, dose escalation-, blocking-, pharmacokinetic- and biodistribution studies (using both fluorescence and radioactivity) were performed, next to imaging of clinically relevant orthotopic xenografts for breast and colorectal cancer. EpCAM-F800 targets EpCAM with high specificity in vitro, which was validated using in vivo blocking experiments with a 10x higher dose of unlabeled Fab. The optimal dose range for fluorescence tumor detection in mice was 1–5 nmol (52–260 μg), which corresponds to a human equivalent dose of 0.2–0.8 mg/kg. Biodistribution showed high accumulation of EpCAM-F800 in tumors and metabolizing organs. Breast and colorectal tumors could clearly be visualized within 8 h post-injection and up to 96 h, while the agent already showed homogenous tumor distribution within 4 h. The blood half-life was 4.5 h. This study describes the development and evaluation of a novel EpCAM-targeting agent and the feasibility to visualize breast and colorectal tumors by fluorescence imaging during resections. EpCAM-F800 will be translated for clinical use, considering its abundance in a broad range of tumor types. Highlights: EpCAM-F800 is a fluorescent anti-EpCAM Fab for intraoperative tumor imaging. EpCAM-F800 targets EpCAM with high specificity in vitro and in vivo . Breast and colorectal tumors could be clearly detected using EpCAM-F800 . The optimal dose range for fluorescence tumor detection in mice was 1–5 nmol. EpCAM-F800 will be translated for clinical use and enter the clinic shortly.